Penning-trap mass measurements of the neutron-rich K and Ca isotopes: resurgence of the N = 28 shell strength - Lapierre, Alain; Brodeur, Maxime; Brunner, Thomas; Gallant, Aaron; Simon, Vanessa Véronique (Physical review. C, Nuclear physics, 2012)
We present Penning-trap mass measurements of neutron-rich 44,47−50K and 49,50Ca isotopes carried out at the TITAN facility at TRIUMF-ISAC. The 44K mass measurement was performed with a charge-bred 4+ ion utilizing the TITAN electron beam ion trap and agrees with the literature. The mass excesses obtained for 47K and 49,50Ca are more precise and agree with the values published in the 2003 Atomic Mass Evaluation (AME’03). The 48,49,50K mass excesses are more precise than the AME’03 values by more than 1 order of magnitude. For 48,49K, we find deviations of 7σ and 10σ, respectively. The new 49K mass excess lowers significantly the two-neutron separation energy at the neutron number N=30 compared with the separation energy calculated from the AME’03 mass-excess values and thus increases the N=28 neutron-shell gap energy at Z=19 by approximately 1 MeV.